Corrective Intertrochanteric Osteotomy of the Femur for Aseptic Necrosis of the Femoral Head after Bloodless Reduction of Congenital Dislocation in School-Age Children - Alpysbaev, Khojaakhmed Shaykhislamovich; Djuraev, Akhror Makhmutovich; Tapilov, Elyar Abduvalievich (RA Journal of Applied Research, 2021)
The immediate results of treatment of 72 children aged 7 to 12 years with aseptic necrosis of the femoral head after bloodless reduction of congenital hip dislocation were analyzed. When treating patients, the following types of surgical treatment were used:extra-articular or open centering of the femoral head with intertrochanteric-torsion-varizing or devarizing and rotational osteotomy of the femur with bringing down the greater trochanter in the caudal direction. In all patients, pain and lameness disappeared, internal rotation of the lower extremities when walking, and the range of motion in the hip joint improved. Improved radiometric parameters characterizing the ratio of the acetabulum and the head of the femur and the angular values ​​of the hip joint and proximal femur.